2016
DOI: 10.4236/ojopm.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Colour Polymeric Film (Starch-Chitosan) Development: Characterization for Packaging Materials

Abstract: Biodegradable starch-based chitosan reinforced composite polymeric films were prepared by casting. The chitosan content in the films was varied from 20% to 80% (w/w). Tensile strength (TS) was improved significantly with the addition of chitosan but elongation at break (EB %) of the composites decreased. Tensile strength of the composites raised more with the addition of the acacia catechu content in the films varied from 0.05% to 0.2% (w/w). The better thermal stability of this prepared film was confirmed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…The SCF becomes more soluble because, after dissolution in acetic acids, the salts of the acid remain inside the d -glucosamine units. The presence of acid salts provides more binding sites for water molecules, and as a result, enhancing the overall solubility of SCFs . The increase in soil degradability can be attributed to the incorporation of glycerol as a plasticizing agent.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCF becomes more soluble because, after dissolution in acetic acids, the salts of the acid remain inside the d -glucosamine units. The presence of acid salts provides more binding sites for water molecules, and as a result, enhancing the overall solubility of SCFs . The increase in soil degradability can be attributed to the incorporation of glycerol as a plasticizing agent.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The presence of acid salts provides more binding sites for water molecules, and as a result, enhancing the overall solubility of SCFs. 45 The increase in soil degradability can be attributed to the incorporation of glycerol as a plasticizing agent. It is known that glycerol is a strong swelling reagent, swelling the SCF in soil conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The interaction mechanism of DE-ChN and GM in nanocomposite lms as can be seen from Figure .4. The addition of polysaccharide enhanced the hydrogen bonding force between GM molecules, thereby increasing the tensile strength of the GM/DE-ChN nanocomposite lm (Mollah et al 2016). According to the data in Table 1, when the addition amount of DE-ChN was 60%, the maximum tensile strength of GM/DE-ChN nanocomposite lm was 107 MPa, which was 343% higher than the original GM lm.…”
Section: Mechanical Properties Of Gm/de-chn Nanocomposite Lmsmentioning
confidence: 99%
“…The SEM The SEM micrograph obtained for the pure chitosan ( Figure 11) revealed that the texture is plain without pores having smooth, compact and homogeneous even surface structure with no gross effects [52].…”
Section: Scanning Electron Microscopic (Sem) Studiesmentioning
confidence: 99%